FIGURE 8. Eurycercus nipponica, female from a in A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska - Bekker, Eugeniya I.; Kotov, Alexey A.; Taylor, Derek J. (Zenodo, 2012)
FIGURE 8. Eurycercus nipponica, female from a swampy area (with a fresh bear trail in time of sampling) near Travianoy Cape, Kurilskoe Lake, Kamchatka Area, Russia A, parthenogenetic female, lateral view. B–C, ephippial female, lateral and anterior view. D, parthenogenetic female, ventral view. E, head. F, dorsal head pores. G, postabdomen. H, its distal portion. I, its basal portion. J, antenna I. K, antenna II. Scale bar denotes 1 mm (A–D); 0.1 mm (E–K). : Published as part of Bekker, Eugeniya I., Kotov, Alexey A. & Taylor, Derek J., 2012, A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska, pp. 1-40 in Zootaxa 3206 (1) on page 26, DOI: 10.11646/zootaxa.3206.1.1, http://zenodo.org/record/5248211